New insights into taphonomic analysis of the Upper Pleistocene Ursus spelaeus bones deposit from Bàsura cave (Toirano, NW Italy) - MARTA ZUNINO; ELISABETTA STARNINI; DANIELE AROBBA; MARCO AVANZINI; PAOLO CITTON; MARCO FIRPO; FABIO NEGRINO; MARCO ROMANO; ISABELLA SALVADOR; IVANO RELLINI (Journal of Quaternary Science, 2022)
The Bàsura Cave (Toirano, NW Italy) became famous worldwide in 1950 for the discovery of prehistoric human footprints and of an impressive Ursus spelaeus bone deposit baptized by the first explorers “Cimitero degli Orsi” (Bear Cemetery). The bear remains belonging to the deeper layer of the deposit have been left in situ and nowadays are one of the principal attractions for visitors. A new research project aimed at re-evaluating the legacy and collections from this important cave involved the taphonomic study of the bones, along with sedimentological, micromorphological analyses and new radiocarbon dates, in order to understand the nature and chronology of the deposit. In the present study, element quantification and surficial state of preservation of the skeletal elements were analyzed to assess the origin of bone accumulation, the composition of the assemblage in terms of age and species, and the representation of the different portions of the carcasses. The bone sorting and orientation along with oxidation pattern and micromorphological data indicate an intense reworking of sediments and bones. The site is to be considered among those known in Europe as representative of the last populations of Ursus spelaeus before the demise of this specie during the Last Glacial Maximum.